The Greatest Debate - Campi, Luigi (ED); Pavlíček, Ota (ED) (Brepols Publishers, 2026)
Quodlibetal debates hosted by liberal arts faculties were among the most important discussions at late medieval universities, resembling modern scientific conferences. All scholars associated with the faculty of liberal arts, including those working in higher faculties, presented lectures and shared their knowledge on contemporary scholarly topics. However, these debates as a genre are little known and largely unexplored. This volume, based on research supported by the European Research Council within the ACADEMIA project, therefore focuses on perhaps the greatest quodlibet ever held, namely the Prague Disputation of 1409, with up to 148 scholars presenting papers, and many more in attendance. The significance of this quodlibet is underscored by its probable two-week duration and its occurrence at a time when the future of knowledge production in Central Europe was being decided: around the end of the quodlibet, the Kuttenberg Decree was issued, leading to the departure of the German masters from Prague and the strengthening of surrounding Central European universities, particularly the University of Leipzig. This volume contextualises the 1409 disputation and delves into the genre of quodlibetal debates at liberal arts faculties more generally. It includes an overview of Central European quodlibeta as a genre, updates the literature on Prague quodlibeta, and offers analysis of selected scholarly topics from the 1409 quodlibet and editions of particular texts associated with it, the last “international” scholarly debate at the University of Prague before the onset of the Hussite wars.